Estudio de prefactibilidad para la instalación de una planta productora de desodorantes naturales con gel de linaza (Linum usitatissimum) - Martinez Pajuelo, Lucero Marisol (2021)
The purpose of this pre-feasibility study is to evaluate and analyze the feasibility of implementing a plant to produce natural deodorants with flaxseed gel, which, thanks to its natural inputs, has benefits for consumers, unlike synthetic deodorants. This product will be presented in 50 ml roll - on containers. The market will be segmented as follows: population of Metropolitan Lima, socioeconomic sectors A and B, people over 18 – 45 years of age, with the need to eliminate body odor. In the first year, the demand for the project amounts to 2 051 674 units, while the last year requires 4 048 522 units. These results were obtained by analyzing apparent internal demand (DIA), demographic and psychographic segmentation, intensity and intention of purchase. After evaluating the market prices and the necessary inputs for production, the sales price per unit will be S/ 9,50, with a production cost of S / 4,89 and sale value of S/ 5,88. The plant will take place in the district of Chorrillos, Lima, with an area of 776.25 m2. This will work 6 days a week, 52 weeks a year, with 1 shift of 8 effective hours. It will have an administrative and productive staff of 5 and 11 people, respectively. In addition, the raw material and supplies will be guaranteed. Regarding the processes, the bottlenecks are packed and packing. Therefore, the installed capacity of the plant will be 7 790 479 units per year. The total investment required for the implementation of the project amounts to S/ 1 730 562, with 40% financed and 60% contributed by investors. Finally, with the economic and financial evaluation, it was possible to demonstrate that the present study is viable. In addition, the ratio B / C and the economic IRR is 2,88 and 62,15%, respectively, while the financial, 4,24 and 81,23%.